Bioactive proteins from Solanaceae as quorum sensing inhibitors against virulence in Pseudomonas aeruginosa. Issue 6 (June 2015) - Singh, Gurpreet; Tamboli, Ekant; Acharya, Aurovind; Kumarasamy, Chellan; Mala, Kanchana; Raman, Pachaiappan
Abstract: Cell-to-cell communication or quorum sensing (QS) is a generic event in bacteria that is used to coordinate gene expression among local populations. The phenomenon of QS depends on the fact that presence of sufficient bacteria ascertains a threshold level of autoinducer concentration that allows bacteria to sense a critical cell mass and to activate or repress target genes. Thus, QS has been an attractive target for the development of anti-infective strategies that are not based on the use of antibiotics. Several anti-QS approaches have been demonstrated including natural products from plant-based secondary metabolites. However, the role of plant bioactive proteins as an anti-QS peptide is yet to be deciphered. Against a backdrop of ever-increasing antibiotic resistant pathogens, there is a strong need for development of alternative therapeutic strategies. Thus, our hypothesis is that bioactive proteins from the plant family Solanaceae are quorum quenching molecules that can be exploited to develop a therapeutic strategy against virulence. We presume that bioactive proteins will inactivate or inhibit or degrade QS signals from bacteria to prevent cell-to-cell communication and thus inhibit development of virulence in Pseudomonas aeruginosa . Further, the use of proteins as quorum quenchers will delay the bacteria to develop resistance against these quenching molecules.